EGS P24 Extended Thromboprophylaxis in the Prevention of Postoperative Venous Thromboembolism after Emergency Surgery. (7th December 2022) - Clements, Caterina; Bezzaa, Sabrina; Patel, Puja; Graham, Gemma; Kersey, James; Nehra, Dhiren; Lewis, Trystan; Jamal, Karim
Abstract: Background: Venous thromboembolism (VTE) after emergency laparotomy is a significant cause of morbidity and mortality. Where extended thromboprophylaxis is used in the post-operative care of patients with colorectal malignancy or pelvic surgery, no such guideline exists for the patient undergoing emergency laparotomy. Arguably emergency laparotomy has one of the highest associated death rates of all types of surgery, greater than that of major elective GI surgery and involves high risk patients. The objective of this study is to ascertain the incidence of symptomatic VTE after emergency laparotomy within current thromboprophylaxis regimens at a district general hospital and consider the benefits of extended regimes in this patient cohort. Methods: A database of all patients who underwent emergency laparotomy over a 12 month period from January 2019 to December 2019 was retrospectively analysed. The primary outcome was the incidence of symptomatic VTE within 90 days of emergency laparotomy. This was cross-referenced to known patient risk factors for thromboembolism. Results: A total of 113 patients underwent emergency laparotomy during this period. Those who had multiple laparotomies and were duplicated or who died were excluded, leaving a total of 94 patients, 55 female and 39 male. 80 patients underwent a VTE prophylaxis regimen using perioperative and postoperative low-molecular-weight heparin (LMWH) based on their weight. The average length of stay was 18 days. 20 patients had an inpatient stay greater than 28 days and, therefore, received extended prophylaxis during their admission. 21 patients were given prolonged anticoagulation on discharge to complete a total of 28 days, 14 of these had suspected cancer intraoperatively, 6 were previously already anticoagulated. The postoperative VTE incidence was 6, 4 were diagnosed during admission and so received prolonged anticoagulation on discharge. 2 patients were not given prolonged VTE prophylaxis on discharge. Conclusions: An extended VTE prophylaxis regimen using low-molecular-weight heparin is simple and effective and an accepted practice in the management of post operative colorectal cancer patients. A randomised control trial is likely needed to further explore the use of extended low molecular weight heparin in the postoperative care of emergency laparotomy patients.